2009
DOI: 10.1088/0953-2048/22/11/114009
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz wave emission from intrinsic Josephson junctions in high-Tcsuperconductors

Abstract: Recently, we experimentally demonstrated that rectangular mesa structures of intrinsic Josephson junctions (IJJ) in Bi 2 Sr 2 CaCu 2 O 8+d (Bi2212) can be used as a compact solid-state generator of continuous, coherent and polarized terahertz (THz) radiation. In the present work, we will exhibit tall mesas (over 600 junctions) which were fabricated using UV lithography, e-beam lithography with photoresist and e-beam lithography with a Ti selective etching technique. We will present measurements of the c-axis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Previous studies provided that electromagnetic wave generated mesas are all in below a certain underdoped level of Bi2212 [7]. In this study, under optimized doping conditions we aimed to investigate powerful terahertz emission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies provided that electromagnetic wave generated mesas are all in below a certain underdoped level of Bi2212 [7]. In this study, under optimized doping conditions we aimed to investigate powerful terahertz emission.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that THz emitting mesas are below a certain underdoped level, which has relatively small critical current in contrast to optimally doped and overdoped Bi2212 [7]. More recently, emission powers of 5 µW and frequencies at the higher harmonics up to 2.5 THz have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…They found that standing waves of the electric field are created through interactions with a hot spot and this effect may have an active role in generating synchronized radiation from intrinsic Josephson junction stacks. In [14] we discussed the dependence of the characteristics of the mesa structures on the oxygen doping level of the Bi2212 crystals and reported that the THz emitting mesas are below a certain underdoped level, which has a relatively small critical current in contrast to optimally doped and overdoped Bi2212. Minami et al [15] reported the radiation characteristics of terahertz radiation emitted from rectangular mesa structures of Bi2212 and they concluded that these devices exhibit enough frequency purity, intensity, and controllability to be suitable for device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 1 mV corresponds to 0.483 THz. However, the operation frequency is restricted by the superconducting gap, so it cannot exceed several hundred gigahertz for the devices made of conventional superconductors [2]. Also, the power emitted from a single junction is too small for practical applications, typically in the order of pW.…”
Section: Introductionmentioning
confidence: 99%